Factors affecting the safe sexual behaviors of Korean young adults by gender: a structural equation model - Nalae Moon; Hyunjin Kang; Su Ji Heo; Ju Hee Kim (Korean Society of Women Health Nursing, 2023)
Purpose The aim of this study was to determine the factors that influence safe sexual behaviors of Korean young adults and identify differences by gender. Methods This study aimed to determine which factors affected safe sexual behaviors based on the Theory of Planned Behavior. Data from 437 Korean young adults (in their 20s and 30s) were collected via online survey between January 3 and January 28, 2022. The questionnaire included items on sexual body image, sexual role perception, sexual attitudes, sexual socialization, sexual communication, and safe sexual behaviors. Structural equation modeling was performed. Results According to the overall model fit of the hypothetical model, the final model was acceptable and explained 49% of safe sexual behaviors. Sexual attitudes (β=-.70, p<.001) and sexual communication (β=.53, p<.001) directly affected safe sexual behaviors, and sexual role perception (β=.42, p<.001) indirectly affected safe sexual behaviors in a combined model. There were gender differences in the path from sexual attitudes (β=-.94, p<.001) and sexual communication (β=.66, p<.001) to safe sexual behaviors and from sexual body image (β=.27, p<.001) to sexual communication. Conclusion Sexual attitudes and sexual communication were predictors of safe sexual behaviors, which differed by gender. Strategies that consider sexual attitudes, sexual communication, sexual role perception, and differences between men and women should be developed to improve the safe sexual behaviors of young adults.